Versatile synthesis of 5-aminoimidazole-4-carboxylic acid derivatives - Dias, Alice (2011)
5-Amino imidazole 4-substituted carboxamidines and 4-substituted imidoyl cyanides were selectively obtained under mild experimental conditions from reaction of the easily accessible 5-amino-4-cyanoformimidoyl imidazoles with primary aliphatic and aromatic amines, ammonia and amino acids in a one-pot reaction. When alcohols were used, the corresponding 5-aminoimidazole 4-carboximidates were isolated. An equally simple reaction occurred when starting imidazoles were combined with water to give 5-aminoimidazole 4-acyl cyanides.